Morfologi Kelenjar Parotis Dan Mandibularis Babi Timor (Sus scrofa domesticus) - Filipe Mali Dos Santos; Inggrid T Maha; Yeremia Y Sitompul; Filphin A Amalo (Jurnal Veteriner Nusantara, 2023)
Timor pig (Sus scrofa domesticus) is classified as one of local Indonesia pigs breed of Sus scrofa. Salivary glands had huge contribution to the digestive system. This research aimed to identify the gross anatomy and histomorphology of the parotid and mandibular glands in Timor pigs. Five samples were taken from Atambua slaughter house. Observation of gross anatomy were carried out directed in slaughter house. Then, the glands were fixated in 10% formalin and stained with HE. The results showed the parotid gland was located on the ventral of the auricle and stretched superficially along the caudal masseter muscle to the caudal of the lower jaw. The parotid gland had brown triangle-shape lobules. The mandibular gland was located in the caudal of the lower jaw or profundus of the parotid gland and had pinkish irregular-shape with rounded edges. The asinar cells of the parotid gland were dominated by serous acini with pyramid-like cells. Serous cells were round-shaped in center of cell membrane. Other serous cells called special serous cells were round-shaped pressed into basal of cell membrane. The asinar cells of the mandibular gland were dominated by mucous acini and discovered serous acini and serous demilune. Pyramid-like mucous cells had flat nucleus in basal of cell membrane. Pyramid-like serous cells had round nucleus in center of cell membrane. Serous cell that arranged in peripheral mucous acini will form into serous demilune. The ducts on the parotid and mandibular glands comprised of the intercalated ducts, the striated ducts and the excretory ducts.